مفهوم الإصلاح في القرآن المجيد: دراسة في أسبابه ومظاهره - إسماعيل الحسني (International Institute of Islamic Thought, 2015)
يتناول هذا البحث كيفية فهم الإصلاح في القرآن الكريم فهماً منهجياً، وذلك بعد إبراز حدود التحليل اللغوي لمفهوم الإصلاح، ثمّ استعراض هذا المفهوم في سياق ما طرحه القرآن الكريم من أسباب تكوّنه، ومظاهر تجسّده. وقد قصرنا النظر في هذا البحث على أمرين اثنين: أولهما التدافع الذي يقابل الجمود، ويسعى صاحبه باستمرار إلى تضييق شقّة التناقض بين الأقوال والممارسات. والثاني التوسّط بوصفه عملاً تحليلياً لواقع الناس، لا فضيلةً أخلاقية فحسب. This article attempts to understand the concept of iṣlaḥ (reform) as presented in the Qur'an in a methodological manner. After highlighting the limits of linguistic analysis of the concept of iṣlaḥ (reform), we have reviewed this concept within the context of the Qur'anic text. We have limited this discussion to two issues: (1) discussion of intellectual struggle as opposed to passive stagnation, seeking to narrow the gap between words and actions; (2) the discussion of moderation (tawassuṭ) as praxis, not simply as a moral virtue.